2018
DOI: 10.1038/s41598-018-28200-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying hormones in exhaled breath for physiological assessment of large whales at sea

Abstract: Exhaled breath analysis is a non-invasive assessment tool that has shown promise in human diagnostics, and could greatly benefit research, management, and conservation of large whales. However, hormone assessment of whale respiratory vapor (blow) has been challenged by variable water content and unknown total volume of collected samples. To advance this technique, we investigated urea (a compound present in narrow range in circulation) as a normalizing factor to correct for blow sample concentration. Normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 68 publications
2
57
0
Order By: Relevance
“…Technologies that are increasingly being used in marine research, such as unmanned aerial vehicles, can also provide non‐invasive monitoring of population size, health, and reproductive status of individuals: for example, by collecting samples from whale blows (exhaled breath) (Burgess et al . ; Johnston ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Technologies that are increasingly being used in marine research, such as unmanned aerial vehicles, can also provide non‐invasive monitoring of population size, health, and reproductive status of individuals: for example, by collecting samples from whale blows (exhaled breath) (Burgess et al . ; Johnston ).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, population estimates of animals in remote locales can be obtained more frequently and more broadly than is possible through traditional survey methods. Technologies that are increasingly being used in marine research, such as unmanned aerial vehicles, can also provide non-invasive monitoring of population size, health, and reproductive status of individuals: for example, by collecting samples from whale blows (exhaled breath) (Burgess et al 2018;Johnston 2019).…”
Section: The Future Of Sentinel Sciencementioning
confidence: 99%
“…A potentially more accessible and repeatable method is to use whale respiratory vapor to assess hormone levels, disease organisms, and microbiome information. Burgess et al (2018) demonstrated the feasibility of using polemounted collection of whale blow for hormone analyses with the caveat that sample concentrations must be normalized as an unknown amount of salt water is mixed with every exhalation (Burgess et al, 2018). UAS collection provides the opportunity to sample while keeping the boat further away from individual whales, Pirotta et al (2017) used a drone to collect an extraordinary diversity and abundance of microbiota from the blow in migrating populations of humpback whales, clearly and unambiguously distinguishing microbial communities from surrounding control seawater and air samples (Pirotta et al, 2017).…”
Section: Methods For Assessing Factors Affecting Right Whale Healthmentioning
confidence: 99%
“…; Burgess et al . ). The temporal signature of the physiological response manifested as concentrations of GCs in these different types of biological samples varies from real‐time (blood) or near real‐time (blow), to hours or days (blubber, feces) or months to years (cerumen, hair, and baleen).…”
Section: The Mean (± Sd) Baseline (± Sd) and Maximum Values For Cormentioning
confidence: 97%
“…Glucocorticoid hormones (GCs) have been analyzed in several sample types in marine mammals, including blood (i.e., serum, plasma), blubber, feces, hair, saliva, exhaled respiratory 1 vapor ("blow"), cerumen (i.e., earwax, ear plug), and baleen (e.g., Hogg et al 2005Hogg et al , 2009Amaral 2010;Rolland et al 2012Rolland et al , 2017St. Aubin et al 2013;Trumble et al 2013;Hunt et al 2014;Kellar et al 2015;Champagne et al 2016;Robeck et al 2017;Burgess et al 2018). The temporal signature of the physiological response manifested as concentrations of GCs in these different types of biological samples varies from real-time (blood) or near real-time (blow), to hours or days (blubber, feces) or months to years (cerumen, hair, and baleen).…”
mentioning
confidence: 99%